Letter (copy) : Ana Maria Gallut Fernandez - Tewson, Vincent
1939-07-17 038-0080-002 International HVT/AEC/MS/1,425 17th July, 1939. Mr. E.E. Brooker, 46, Kingsway, LONDON, W.C.2. Dear Mr. Brooker, ANA MARIA GALLUT FERNANDEZ. I have your letter of the 15th July with regard to the case of the above child. Mr. Gallut wrote to us direct on behalf of his daughter requesting us to take steps to ensure that she should not be repatriated to Spain. We telephoned Mrs. Curtis, principal of the school at which Ana Maria was staying, and we were informed that Mr. Gallut had written to Mrs. Curtis to the efect that he and his whole family had a possibility of being selected for emigration to Mexico. In the event of his being successful they would have to leave France very quickly and for this reason Mr. Gallut expressed his desire to have his children sent back to join him and his wife in France. Mrs. Curtis thereupon cast about for means of ensuring the girl (and her brother) a safe journey back to their parents. She learned that a convoy was leaving England tomorrow, Tuesday, and made arrangements for them to join it. I understand she has given a further sign of her interest in the family in that she has sent Mr. Gallut a sum of money which should enable him and his wife to meet the convoy at the port of arrival in France. I may say when the case first came under my notice it was my intention to take some such step as indicated 292/946/38/80(II)